PENGARUH STRUKTUR MODAL, KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA - Angga Dwi Pratama, 14.05.52.0003; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2019)
This study examines the effect of capital structure, independent commissioners, managerial ownership, institutional ownership and firm size on earnings quality. The sample in this study used 104 data from 26 manufacturing companies listed on the Indonesia Stock Exchange for the period 2014-2017 by using purposive sampling method. The analysis tools used are normality test, classical assumption test, multiple linear regression test, model test and hypothesis test. Based on the research that has been done, the results of this study showed that frim size have a significant positive effect on earnings quality, capital structure and independent commissioners have a significant negative effect on earnings quality. While managerial ownership and institutional ownership have no significant effect on earnings quality.